2016
DOI: 10.1016/j.aap.2015.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary research developing a theory of cell phone distraction and social relationships

Abstract: Motor vehicle crashes remain the leading cause of death and injury for people aged 5 – 34, accounting annually for over 3000 deaths, and 100 times as many injuries. It is well established that distracted driving, and cell phone use while driving in particular, pose significant crash risk to drivers. Research has demonstrated that drivers are well aware of this danger but over 90% of drivers report using a cell phone while driving. Given the likely role that social influence plays in how people use cell phones … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 14 publications
3
16
0
Order By: Relevance
“…Most (70%) peers were similarly aged (1920) to the participants in W4; 76% were friends, 15% were siblings, and 10% were other family members or romantic partners. Peer cell phone use is described in Table 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most (70%) peers were similarly aged (1920) to the participants in W4; 76% were friends, 15% were siblings, and 10% were other family members or romantic partners. Peer cell phone use is described in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Another survey indicated that teens recognize that secondary task engagement, particularly cell phone use such as texting, and mobile application use (such as Twitter, Snapchat, Instagram) contribute to driver inattention; however, they and their peers often engage in these behaviors while driving (18). Texting among young drivers may increase with age and experience and vary according to the age of passenger (19). …”
Section: Introductionmentioning
confidence: 99%
“…The proximity of relationship of the individual who is communicating with the adolescent influences cell-phone use (Atchley & Warden, 2012; LaVoie, Lee, & Parker, 2015). In a focus group study, adolescent participants indicated that context mattered; the individual involved in the communication, and the reason behind it, would influence whether they would use the cell phone while driving (McDonald & Sommers, 2015).…”
Section: Risk Factors For Engagement: Development Peers and Familiesmentioning
confidence: 99%
“…In a focus group study, adolescent participants indicated that context mattered; the individual involved in the communication, and the reason behind it, would influence whether they would use the cell phone while driving (McDonald & Sommers, 2015). A survey study of 395 adolescent drivers found that adolescents most often spoke to parents while driving (50%), rather than a significant other (16%) or friend (21%) (LaVoie et al, 2015). This indicates that reducing check in calls from parents may reduce cellphone use while driving.…”
Section: Risk Factors For Engagement: Development Peers and Familiesmentioning
confidence: 99%
See 1 more Smart Citation